Evaluation of Shrimp Waste Meal as a Probable Animal Protein Source for Broiler Chickens - Okoye, F.C.; Ojewola, G.S.; Njoku-Onu, K. (International Journal of Poultry Science, 2005)
Sixty unsexed Anak broiler chickens were used to evaluate the effect of dietary inclusion of Shrimp waste meal (swm) in broilers diet. They were randomly allotted to four treatment diets which were both isocaloric and isonitrogenous. The text ingredient was included in the four diets at 0.0%, 10%, 20% and 30% respectively for diets 1, 2, 3 and 4, both at the starter and finisher phases. There were 15 birds per treatment and 5 birds per replicate. The trial lasted 8 weeks. The result showed that the dietary treatments had significant (p<0.05) effects on body weight gain, feed intake and feed-to-gain ration at the starter phase while the feed-to-gain ratio and weight gain were not significant (p>0.05) influenced at the finisher phase. At the starter and finisher phases, average body weight gain ranged from 446.56 to 600.00g/bird and 1096.67 to 1166.67g/bird with corresponding average total feed intake which ranged from 1318.00 to 1462.42g/bird and 2712.00 to 2880.00g/bird. Birds fed diets 1 and 2 had statistically comparable weight gain while those fed diets 3 and 4 were depressed at the starter phase. At the finisher phase all the diets were comparable. The study revealed that swm is a valuable animal protein source for broilers and can be included up to 10% in both starter and finisher broiler diets.